Kualitas Pelayanan Publik di Nagari Panti Timur Kecamatan Panti Kabupaten Pasaman - Weni Artitantia; Roni Ekha Putera; Yoserizal Yoserizal (Department of Public Administration, Universitas Negeri Surabaya, 2022)
The purpose of this study was to describe the quality of public services in the Office of the Wali Nagari Panti Timur. The study was conducted on public services, especially in the Business Certificate (SKU). With this research, it is hoped that the Nagari Panti Timur government can provide quality services effectively and efficiently in order to achieve public satisfaction. The theory that is used is the public service quality theory with three variables, namely efficiency, responsiveness, and non-partisanship. Data collection methods used are interviews, observation and documentation. Interview informants were selected using purposive sampling method and accidental sampling method. To obtain data validity, researchers triangulated data sources. This study found that the quality of public services at the Wali Nagari Panti Timur Office, especially in making Business Certificates (SKUs) so far has not been carried out well. The three variables, namely efficient, responsive, and non-partisan, have not been fully achieved. Based on the results of the research conducted, it was found that the level of discipline of the Nagari apparatus was still low and often arrived late, the lack of clarity of information related to service standards which caused confusion for service users, and the suggestion box was broken making it difficult for the process of submitting public complaints to the Nagari Panti Timur government.